From legacy to digital native media: How Indonesian journalists perceive these working structure differences - Muthmainnah, Amalia Nurul; de-Lima-Santos, Mathias Felipe (Jurnal Komunikasi, 2025)
The rise of digital native media has transformed the news ecosystem in the last decades. However, actors involved in the deployment of these digital media organizations mostly come from traditional publishers with established routines, norms, and practices. In Indonesia, digital native media as a flourishing industry is distinguished sharply from the old media, once they are large as online, grassroots, and anti-establishment forms of media. Through ten (n=10) semi-structured interviews, this study analyzed the changes that professionals have faced when moving from legacy (broadcast and print) media organizations to digital native media. Results show that Indonesian digital native media organizations bring Western ideas to develop their business models, driven in particular by innovative, technology-focused, startup values. However, these outlets face challenges related to building a solid reputation and brand recognition in comparison to legacy publishers, which limits their reach to people in the higher echelons.